2001
DOI: 10.1002/ajmg.10066
|View full text |Cite
|
Sign up to set email alerts
|

Dominant paternal transmission of Cornelia de Lange syndrome: A new case and review of 25 previously reported familial recurrences

Abstract: The Cornelia de Lange syndrome (CdLS) is an autosomal dominant multisystem disorder characterized by somatic and cognitive retardation, characteristic facial features, limb abnormalities, hearing loss, and other organ system involvement. The vast majority of cases (99%) are sporadic, with rare familial occurrences having been reported. Most individuals with CdLS do not reproduce as a result of the severity of the disorder. Maternal transmission has been well documented, as have several cases of multiple-affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 41 publications
3
48
0
2
Order By: Relevance
“…This means that approximately one-third of the coding sequence was sampled in 45 individuals and more than one-half of the proximal intronic sequence was also sampled for splicing mutations. On the basis of observed relative frequencies of splice site mutations and other mutations in large multiexon genes, and assuming that all affected individuals are heterozygotes (as expected from the strong evidence for autosomal dominant transmission 26 ) and that there are no strong mutational hot spots in the coding sequence, the identification of 9 mutations in a panel of 45 individuals with CdLS ( Table 1) equates roughly to a detection rate >50%. The relatively low mutation detection rate could reflect limitations of the mutation screening protocol: only coding sequences and proximal intronic sequences were analyzed, and the gene is large and possibly prone to undetected large-scale mutations.…”
Section: Methodsmentioning
confidence: 99%
“…This means that approximately one-third of the coding sequence was sampled in 45 individuals and more than one-half of the proximal intronic sequence was also sampled for splicing mutations. On the basis of observed relative frequencies of splice site mutations and other mutations in large multiexon genes, and assuming that all affected individuals are heterozygotes (as expected from the strong evidence for autosomal dominant transmission 26 ) and that there are no strong mutational hot spots in the coding sequence, the identification of 9 mutations in a panel of 45 individuals with CdLS ( Table 1) equates roughly to a detection rate >50%. The relatively low mutation detection rate could reflect limitations of the mutation screening protocol: only coding sequences and proximal intronic sequences were analyzed, and the gene is large and possibly prone to undetected large-scale mutations.…”
Section: Methodsmentioning
confidence: 99%
“…1 The majority of the cases are sporadic, but a few cases showing an autosomal-dominant inheritance have been reported. 2 Two recent studies reported mutations in the NIPBL gene to cause CdLS 3,4 and NIPBL mutations have previously been identified in 26 -56% of CdLS cases. 4 -8 NIPBL is located on chromosome 5p13, consists of 47 exons and encodes delangin, a 2804 amino-acid protein which is the homolog of fungal Scc2-type sister chromatid cohesion protein and the Drosophila Nipped-B developmental regulator.…”
Section: Introductionmentioning
confidence: 99%
“…The low estimates for the general recurrence risk for sibs ( Jackson et al 1993 ) argues against recessive inheritance and, in some of the multicase pedigrees, there is strong evidence for autosomal dominant inheritance ( KrajewskaWalasek et al 1998 ;Kozma 1996 ;McKenney et al 1996 ;Russell et al 2001 ;McConnell et al 2003 ). In other multi-case pedigrees, the birth of more than one affected child to unaffected parents can be explained by gonadal mosaicism.…”
Section: Introductionmentioning
confidence: 99%